Optimizing Community Aspiration Processes by Village Consultative Bodies: Optimasi Proses Aspirasi Masyarakat Melalui Badan Musyawarah Desa - Serly Febriyana; Muhammad Habibi; Ahmad Yani; Deandlles Christover (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The absorption of community aspirations is a key indicator in establishing participatory and responsive village governance. Specific Background: In Bukit Raya Village, the Village Consultative Body (BPD) plays a central role as a liaison between the community and the village government, yet faces obstacles such as limited resources and low public participation. Knowledge Gap: While numerous studies have examined the general role of BPD, empirical research that specifically details the stages of aspiration absorption and the supporting or inhibiting factors at the village level remains scarce. Aims: This study analyzes the process of aspiration absorption by the BPD in Bukit Raya Village through four stages—identifying, accommodating, managing, and channeling aspirations—and identifies factors influencing its effectiveness. Results: Using a qualitative method and Miles and Huberman’s interactive analysis, the findings reveal that although cross-stakeholder synergy is relatively effective, the BPD lacks a formal method for collecting aspirations and faces challenges in participation, public understanding, and human resource capacity. Novelty: This research offers a detailed mapping of the stages and determining factors for successful aspiration absorption at the village level. Implications: The findings underscore the urgency of strengthening human resource capacity, participation mechanisms, and cross-sector collaboration to optimize the BPD’s role in achieving inclusive and sustainable village development. Highlights: Identifies four key stages of aspiration absorption. Reveals gaps in participation and resource capacity. Proposes strategies for inclusive and sustainable governance. Keywords: Village Consultative Body, Community Aspirations, Public Participation, Rural Governance, Sustainable Development